Accessibility to Credit and its Determinants: A State-level Analysis of Cultivator Households in India. (August 2014) - Bhattacharjee, Manojit; Rajeev, Meenakshi
It is well known that around 80 per cent of farmers in India are in the small or marginal farmers group which requires financial resources on a regular basis for their farming activities. Needless to say, as these households do not possess adequate savings, accessibility to financial resources at reasonable terms and conditions from financial intermediaries becomes a crucial parameter for their productive activities and hence, in turn, their well-being. Based on the 59th round of household-level data from the Debt and Investment Survey and the Situation Assessment Survey (SAS) of farmers provided by the National Sample Survey Organisation (NSSO) of India, this article examines the nature of exclusion faced by farmer households in credit markets across selected prominent states of India. This is done by constructing an indicator, namely, the 'incidence of borrowing'. This article also tries to identify the factors that explain exclusion from access to financial resources by developing a methodology for the detection of credit exclusion. Our results show that the relation between the cost of credit (interest rate) and access to credit depends heavily on the extent of prevalence of informal lenders in a region. JEL Classification: O1, O2